Immunoglobulin somatic hypermutation has clinical impact in DLBCL and potential implications for immune checkpoint blockade and neoantigen-based immunotherapies. Issue 1 (22nd October 2019) - Xu-Monette, Zijun Y.; Li, Jianyong; Xia, Yi; Crossley, Beryl; Bremel, Robert D.; Miao, Yi; Xiao, Min; Snyder, Thomas; Manyam, Ganiraju C.; Tan, Xiaohong; Zhang, Hongwei; Visco, Carlo; et al.
Abstract : Background: Diffuse large B-cell lymphoma (DLBCL) harbors somatic hypermutation (SHM) in the immunoglobulin heavy chain and light chain variable region genes, IGHV and IGK/LV. Recent studies have revealed that IGV SHM creates neoantigens that activate T-cell responses against B-cell lymphoma. Methods: To determine the clinical relevance of IGV SHM in DLBCL treated with standard immunochemotherapy, we performed next-generation sequencing of the immunoglobulin variable regions and complementarity determining region 3 (CDR3) for 378 patients with de novo DLBCL. The prognostic effects of IGV SHM and ongoing SHM or intra-clonal heterogeneity were analyzed in the training (192 patients), validation (186 patients), and overall DLBCL cohorts. To gain mechanistic insight, we analyzed the predicted IG-derived neoantigens' immunogenicity potential, determined by the major histocompatibility complex-binding affinity and the frequency-of-occurrence of T cell-exposed motifs (TCEMs) in a TCEM repertoire derived from human proteome, microbiome, and pathogen databases. Furthermore, IGV SHM was correlated with molecular characteristics of DLBCL and PD-1/L1 expression in the tumor microenvironment assessed by fluorescent multiplex immunohistochemistry. Results: SHM was commonly found in IGHV and less frequently in IGK/LV. High levels of clonal IGHV SHM (SHM high ) were associated with prolonged overall survival in DLBCL patients, particularly those without BCL2 or MYC translocation. In contrast, long heavy chain CDR3 length, the presence of IGHV ongoing SHM in DLBCL, and high clonal IGK/LV SHM in germinal center B-cell–like (GCB)-DLBCL were associated with poor prognosis. These prognostic effects were significant in both the training and validation sets. By prediction, the SHM high groups harbored more potentially immune-stimulatory neoantigens with high binding affinity and rare TCEMs. PD-1/L1 expression in CD8 + T cells was significantly lower in IGHV SHM high than in SHM low patients with activated B-cell–like DLBCL, whereas PD-1 expression in CD4 + T cells and PD-L1 expression in natural killer cells were higher in IGK/LV SHM high than in SHM low patients with GCB-DLBCL. PD-L1 / L2 (9p24.1) amplification was associated with high IGHV SHM and ongoing SHM. Conclusions: These results show for the first time that IGV SHM high and ongoing SHM have prognostic effects in DLBCL and potential implications for PD-1/PD-L1 blockade and neoantigen-based immunotherapies.